If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+33=-3(x+7)
We move all terms to the left:
9x+33-(-3(x+7))=0
We calculate terms in parentheses: -(-3(x+7)), so:We get rid of parentheses
-3(x+7)
We multiply parentheses
-3x-21
Back to the equation:
-(-3x-21)
9x+3x+21+33=0
We add all the numbers together, and all the variables
12x+54=0
We move all terms containing x to the left, all other terms to the right
12x=-54
x=-54/12
x=-4+1/2
| 7=x÷7-2 | | 34=2c+2+c+2 | | -9x+33=-3(x-1) | | 4w-14w=60 | | 4x(3x-7)=32 | | 6(x=4)=20 | | 1/2x+1=1/2x-1 | | X-9=-69+6x | | 25x2=-35x+8 | | 15x2+22x+8=0 | | 10+7x=-6x-146 | | 4+7+2x=24 | | 7x+10=120 | | 6x-10=3x-13 | | 32-6x=8x+12 | | 4+7+3x=24 | | 3x−5=7x−7 | | 15x2+30x-2145=0 | | 9=7x-40 | | 4^3X4^3=4^3x4^3 | | 29.5-5.5x=7.5(3x+3,5) | | 6x-2=39+6 | | Y=22-9x= | | x+3/4x=x-4/4x+3 | | 5(5+1.7x)=5(4.15+1.95x) | | 7/8*x=64 | | 12(x+3)=2(6x-5)+46 | | n=7n | | x^+12x+20=0 | | 66=(22/7)r^2 | | 4b+3b=8 | | 17x+2=5x+50 |